212k views
0 votes
3.5(x + 2) - 6.5 - 2.5(x - 4)

Please help and show work!!

User Ozgur
by
4.7k points

1 Answer

1 vote

Hi Angel018642,

Solution:

3.5(x + 2) - 6.5 - 2.5(x - 4)

= (3.5) (x) + (3.5) (2) + −6.5 + (−2.5) (x) + (−2.5) (−4)

= 3.5x + 7 + −6.5 + −2.5x + 10

=3.5x + 7 + −6.5 + −2.5x + 10

= (3.5x + −2.5x) + (7 + −6.5 + 10)

= x + 10.5

Final Answer:

x + 10.5

User Robi Kumar Tomar
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.